Specialist physician knowledge of chronic kidney disease: A comparison of internists and family physicians in West Africa - Emmanuel I. Agaba; Patricia A. Agaba; Musa Dankyau; Maxwell O. Akanbi; Comfort A. Daniyam; Edith N. Okeke; Antonios H. Tzamaloukas (AOSIS, 2012)
Background: Postgraduate training is aimed at equipping the trainee with the necessary skills to practise as an expert. Non-nephrology specialist physicians render the bulk of pre-end-stage renal disease care for patients with chronic kidney disease (CKD). We sought to ascertain the knowledge of CKD amongst non-nephrology specialist physicians who serve as trainers and examiners for a training, accrediting and certifying body in postgraduate medicine in West Africa. We also compared the knowledge of family physicians and non-nephrology internists. Methods: Self-administered questionnaires were distributed to non-nephrology specialist physicians who serve as examiners for the West African College of Physicians. Results: Only 19 (27.5%) of the respondents were aware of the Kidney Disease Outcomes Quality Initiatives guidelines for CKD management. Twenty five (36.2%) of the respondents had adequate knowledge of CKD. There was no significant difference in the proportion of family physicians and non-nephrology internists who had adequate knowledge of CKD (27.3% vs. 40.4% respectively; p = 0.28). Hypertension and diabetes mellitus were identified by all of the physicians as risk factors for CKD. Non-nephrology internists more frequently identified systemic lupus erythematosus as a risk factor for CKD, urinalysis with microscopy as a laboratory test for CKD evaluation, and bone disease as a complication of CKD than family physicians. Conclusion: There is a lack of adequate CKD knowledge amongst non-nephrology specialist physicians, since many of them are unaware of the CKD management guidelines. Educational efforts are needed to improve the knowledge of CKD amongst non-nephrology specialist physicians. Guidelines on CKD need to be widely disseminated amongst these physicians.